2013
DOI: 10.3390/ijms14047959
|View full text |Cite
|
Sign up to set email alerts
|

Specific siRNA Targeting Receptor for Advanced Glycation End Products (RAGE) Decreases Proliferation in Human Breast Cancer Cell Lines

Abstract: Receptor for Advanced Glycation End Products (RAGE) is an oncogenic trans-membranous receptor overexpressed in various human cancers. However, the role of RAGE in breast cancer development and proliferation is still unclear. In this study, we demonstrated that RAGE expression levels are correlated to the degree of severity of breast cancer. Furthermore, there is a decrease in the proliferation of all sub-types of breast cancer, MCF-7, SK-Br-3 and MDA-MB-231, as a result of the effect of RAGE siRNA. RAGE siRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 58 publications
1
31
1
Order By: Relevance
“…In a similar study conducted by Radia et al, it was discovered that on treating breast cancer cell lines of MCF-7, SK-Br-3 and MDA-MB-231 with RAGE siRNA, the tumor cells failed to progress beyond G1 phase of cell cycle [35]. Another study conducted by Lata K et al involving the treatment of MCF-7 breast cancer cells with 17α-EE enhances the expression of estrogen receptor related receptor gamma (ERRγ, a member of nuclear hormone receptor superfamily) followed by enhanced level of oxidative stress and subsequent activation of the transcription factor, nuclear factor kappa-B (NF-кB) (Fig.…”
Section: Receptor For Advanced Glycation End Products Enhances Prolifmentioning
confidence: 87%
“…In a similar study conducted by Radia et al, it was discovered that on treating breast cancer cell lines of MCF-7, SK-Br-3 and MDA-MB-231 with RAGE siRNA, the tumor cells failed to progress beyond G1 phase of cell cycle [35]. Another study conducted by Lata K et al involving the treatment of MCF-7 breast cancer cells with 17α-EE enhances the expression of estrogen receptor related receptor gamma (ERRγ, a member of nuclear hormone receptor superfamily) followed by enhanced level of oxidative stress and subsequent activation of the transcription factor, nuclear factor kappa-B (NF-кB) (Fig.…”
Section: Receptor For Advanced Glycation End Products Enhances Prolifmentioning
confidence: 87%
“…We documented that RAGE is highly expressed in human TNBC and murine breast cancer cell lines and weakly expressed in low metastatic ER+ cells. However, there are some conflicting reports regarding the expression of RAGE in the MCF7 cell line (40-41). It could be due to the difference in the techniques which were employed.…”
Section: Discussionmentioning
confidence: 99%
“…Using a genetic approach, we showed that RAGE ablation significantly reduced PyMT cell-derived tumor growth while blocking RAGE with neutralizing antibodies inhibits breast cancer visceral metastasis in preclinical mouse models. It has been shown recently that RAGE knockdown by siRNA significantly inhibited tumorigenic potential of MDA-MB231 cell line (40). RAGE ablation in a triple transgenic model of spontaneous pancreatic cancer has also been shown to delay pancreatic cancer development (9,43).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that the targeting of RAGE by specific small interfering RNAs (siRNAs) in different breast cancer cell lines decreased the proliferation of all subtypes of breast cancer [37]. …”
Section: Discussionmentioning
confidence: 99%